O envolvimento do aluno no processo de ensino - aprendizagem durante a realização de atividades experimentais - Serafim Junior, Irineu Modes (2005)
This work had as an objective to identify the motivation level of the students who belong to three public grade schools in the city of São Carlos with different socio-economical realities for the chemistry learning. Experimental activities were developed with the main objective of promoting the student s interaction with their friends and teachers. During the accomplishment of these experimental activities, it was also sought to arive the student s alternative conceptions of those who participated in the research, once this class type is quite favorable for discussions and spontaneous manifestations that has as a base the previous knowledge regarding the phenomenon in observation. At the end of the offered mini-courses, the students were invited to act as voluntary monitors in the chemistry classes in their own school. It was observed that the number of monitors that participated in the project, in relation to the total number of students, was very small in the outlying school and in the schools of central location. When compared by their shifts, the smallest number of participants was of students of the night period, probably due to the fact of they are hard-working students, in their majority. Establishing a comparison among the students from the different schools, a percentile adult of the students of the central schools participation was observed, once these students seem to be more motivated for learning. In the three schools, the monitorship activity was shown to be a motivation factor for the learning. All the monitors wrapped up in the project and they really helped in the laboratory classes, playing an active part in the teaching-learning process. Differences were also verified in the students of the three public schools profile, what signals for the importance of accomplishing more consistent studies on the profile of the schools before the definition of public politics for the teaching.